Bio-structural analogues in architecture - Lim, Joseph (Amsterdam : BIS Publishers, 2009)
Documents a series of design experiments on structural prototypes derived from biological systems in order to reveal mechanical and structural analogs of a spatial character.
Includes bibliographical references.
ARC
Keywords: Architecture and biology; Architectural design -- Research; Structural design